Ethnoscience in vernacular architecture of Dayak traditional houses: A study of local knowledge as contextual science learning resources. - Nurussaniah Nurussaniah (Jurnal Pendidikan Informatika dan Sains, 2025)
Science learning in Indonesia is frequently delivered in an abstract manner that is detached from the cultural environment of learners, a condition that contributes to weak scientific literacy and limited appreciation of local wisdom. This study aims to identify the indigenous science embedded in the vernacular architecture of Dayak traditional houses and to reconstruct it into scientific concepts that can serve as contextual science learning resources. The study applied a qualitative descriptive design using an ethnoscience reconstruction approach. Data were gathered through literature study and documentation analysis of architectural features of the Dayak longhouse, namely the rumah betang and rumah radakng of Kalimantan, and were analysed through the stages of identifying indigenous knowledge, reconstructing it into scientific knowledge, and mapping it to the science curriculum. The findings reveal that core architectural elements carry rich scientific content. The elevated stilt structure encodes concepts of pressure, fluid statics, flood hydrology, and structural equilibrium. The use of ironwood relates to material density, mechanical strength, and biological decay resistance. The steep gable roof, the wooden peg joinery, the cross-ventilated and slatted floor, and the natural pigments respectively embody concepts of inclined-plane forces, elasticity and energy dissipation, convective heat transfer and the stack effect, and the chemistry of pigments. These reconstructed concepts align with topics in physics, chemistry, biology, and earth science across the secondary curriculum, and they fit project-based and inquiry learning that strengthens scientific literacy, cultural literacy, and the values of the Pancasila Student Profile. The study concludes that Dayak vernacular architecture is a strong and underused contextual learning resource that connects scientific reasoning with cultural identity and conservation values.